FAKTOR DETERMINAN PADA KETUBAN PECAH DINI - Fitriyani, Fitriyani; Yuniarti, Yuliana Lubis, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Every year the incidence of premature rupture of membranes ranges from 5-10% of all preterm preterm births and membranes occurring in 1% of all pregnancies.70% of cases of premature rupture of membranes occur in early pregnancy, prematurerupture of membranes is the cause of preterm birth as much as 30% (Manuaba, 2010). Atthe Derah Kepahiang General Hospital, the incidence of premature rupture of membranesis 219 cases in 2016.This research is analytical descriptive research with case controldesign. The sample in this study amounted to 138 people divided into two groups of 69cases and 69 controls. Statistical test using chi square test and binary logisticregression.Results of the study of 69 people with premature rupture of membranes atmaternal age <20 and> 35 years (46.4%), primiparity and grandemultipara parity(62.3%), fetal abnormalities (33.3%), gestational age aterm ( 63.8%) and those with ahistory of premature rupture (18.8%) in Kepahiang Hospital by 2016. Maternal age (pvalue0.013 OR = 2.646), parity (p-value 0.0,0 OR OR = 3.111) (p-value 0,0017 OR =2,950), gestational age (p-value 0,386) and history of premature rupture (p-value 0,167)at Kepahiang Hospital 2016. The most dominant factor causing premature rupture ofmembranes in RSUD Kepahiang year 2016 is parity (Exp (B) 2,806).It is expected thatthe hospital can use the research as input to suppress the incidence of premature ruptureof membranes, by counseling to explain the risk factors of premature rupture ofmembranes, especially maternal age, parity and fetal abnormalities.